LED lamp bead, preparation method thereof and LED lamp strip
By employing technologies such as high-purity alumina substrates and precision-processed conductive-optical dual-functional layers, flip-chip Micro-LED chips, and quantum dot optical layers, the problems of poor heat dissipation, low luminous efficiency, and uneven light emission in LED lamp beads have been solved, achieving LED lamp beads with efficient heat dissipation, uniform light emission, and long lifespan.
Patent Information
- Application Number
- CN202511289170.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-10
- Publication Date
- 2026-02-03
AI Technical Summary
LED chips suffer from problems such as poor heat dissipation, low luminous efficiency, uneven light emission, and short lifespan, resulting in inconsistent quality of LED light strip products and hindering the development of the industry.
It employs a high-purity alumina transparent ceramic substrate, magnetron sputtering deposition of indium tin oxide thin film, flip-chip Micro-LED chip, quantum dot optical layer, gradient package and photothermal integrated structure, and through precision process to form a conductive-optical dual-functional layer, microelectrode array, quantum dot self-filled porous protective layer, multi-channel heat dissipation system and optical control, and optimizes circuit layout and light path.
It improves the heat dissipation efficiency and light emission uniformity of LED beads, extends their service life, enhances luminous efficiency and color gamut coverage, and ensures high brightness and stability.
Smart Images

Figure 047B6C0F-677F-4AC5-82EA-C8BFC4A3F543 
Figure 91ECECFA-4CCE-4AB3-BF52-F6ADA03AB872 
Figure BBD3E542-D2F2-44D0-9671-8E7DEDF93C5F
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of LED lamp beads, and particularly relates to an LED lamp bead, a preparation method thereof and an LED lamp strip. BACKGROUND
[0002] As a core component of an LED lamp strip, the performance of an LED lamp bead directly determines the light-emitting efficiency, reliability and application scenario of the LED lamp strip. With the development of automobile lighting and intelligent furniture, the demand for high-quality LED lamp beads is continuously increasing. In 2024, the global LED lamp bead market size reached 354.48 million US dollars, and it is expected to exceed 160 billion US dollars in 2030. At present, due to the long use time and high heat use environment of LED lamp beads, the current LED lamp beads have problems such as poor heat dissipation, low light-emitting efficiency, uneven light emission and short service life, which seriously affect the comprehensive performance and market application of LED lamp strip products. At the same time, thioxyl silicone glue is a modified organic silicon polymer material, which can obtain a coating with different optical properties by doping different substances, and becomes the core candidate of the new generation of LED lamp bead materials.
[0003] However, the current LED lamp bead technology development is faced with the core challenge that the LED lamp bead has problems such as poor heat dissipation, low light-emitting efficiency, uneven light emission and short service life, which ultimately leads to uneven quality of LED lamp bead products, and seriously restricts the economic and technological development of the LED lamp bead industry. SUMMARY
[0004] The first aspect embodiment of the present application provides an LED lamp bead, which is composed of a transparent conductive substrate, a light-emitting unit, a quantum dot optical layer, a gradient encapsulation body, a light-heat integrated structure and a driving and optical regulation. In this way, the problems of poor heat dissipation, low light-emitting efficiency, uneven light emission and short service life of the LED lamp bead are solved.
[0005] The second aspect embodiment of the present application provides a preparation method of an LED lamp bead, which comprises the following steps: A high-purity alumina transparent ceramic substrate is selected, an indium tin oxide thin film layer is deposited by magnetron sputtering, a microelectrode circuit is formed by photolithography and etching, and an array type die bonding area is formed on the surface of the substrate.
[0006] It can be understood that the embodiments of the present application provide thermal-mechanical stability and high-frequency signal integrity by virtue of low thermal expansion coefficient and dielectric constant of high-purity alumina substrate, and the transparency and refractive index thereof match indium tin oxide film to reduce interface light loss. The magnetron sputtering deposition of the indium tin oxide film utilizes argon plasma to bombard an indium tin oxide target, and the carrier concentration is regulated by oxygen doping to realize low sheet resistance and high light transmittance, thereby providing a conductive-optical dual-functional layer for the electrode. The photolithography etching adopts ultraviolet exposure and aqua regia wet etching to selectively dissolve the indium tin oxide, thereby forming a microelectrode with a line width less than 2 μm, and anisotropic etching ensures circuit accuracy; array-type die bonding area photolithography is enhanced by secondary alignment and oxygen plasma surface activation to enhance the wetting property of the solder paste, thereby providing high-precision positioning and reliable electrical connection for LED chip bonding.
[0007] The flip-chip Micro-LED chip is directly soldered to the die bonding area electrode soldering point by tin-silver solder paste, and the chip mounting angle is adjusted to 15°-30°.
[0008] It can be understood that the flip-chip Micro-LED chip adopts an electrode-down structure, is directly soldered to the die bonding area electrode soldering point by tin-silver solder paste, omits the traditional gold wire bonding process, shortens the current path and reduces the series resistance, and at the same time, the heat dissipation efficiency is improved by direct contact of the metal soldering point. The angle adjustment utilizes the optical reflection principle, calculates the included angle between the chip light emitting surface and the substrate normal, optimizes the critical angle of total reflection, makes more light escape from the chip sidewall, improves the light extraction efficiency, and reduces the light crosstalk between adjacent pixels.
[0009] The substrate surface is photolithographically patterned with a microchannel array, the capillary force drives the filling of cadmium selenide / zinc sulfide quantum dot solution, spin-coats ZIF-8 metal organic framework precursor, in-situ crystallization forms a 500 nm porous protective layer at 150-180°C, covers the thioxyl silicone adhesive doped with fluorescent powder, and solidifies at 150°C for 30 minutes to form a quantum dot optical layer.
[0010] It can be understood that the microchannel array utilizes capillary force to achieve precise filling of cadmium selenide / zinc sulfide quantum dot solution, ensures pixelation uniformity, and after spin-coating of ZIF-8 metal organic framework precursor, in-situ crystallization forms a 500 nm porous protective layer at 150-180°C, the pore size of 2-3 nm can selectively adsorb quantum dot surface ligands, and the coordination between Zn 2 ⁺ and quantum dot thiol ligands stabilizes the quantum dot position, the porous structure reduces light scattering loss, improves light transmittance, and the thioxyl silicone adhesive doped with fluorescent powder forms a composite optical layer after solidification, the crosslinked network Si-O-Si bond provides mechanical support, the fluorescent powder and quantum dots cooperatively emit light, the blue light is converted into green / red light through resonance energy transfer based on the Foster principle, color gamut coverage is provided, and the hydrophobicity of ZIF-8 blocks water and oxygen permeation, thereby prolonging the quantum dot lifetime.
[0011] Thiosiloxane glue as the matrix, doped with 8-12wt% nano ZrO2 and 4-8wt% fluorine modified polyimide microspheres, added with 2-4wt% SiO2@TiO2 core-shell light diffuser, mixed and vacuum degassed, degassed for 5 minutes under-0.1MPa, injected into the lens mold and formed a refractive index gradient by gradient centrifugation, then UV pre-cured to lock the gradient distribution, and then 150℃ thermal curing for 20 minutes to complete the packaging of the quantum dot optical layer.
[0012] It can be understood that the embodiments of the present application provide mechanical support through the thiosiloxane glue matrix with its flexible Si-O-Si network structure, and at the same time the thiol groups can form coordination bonds with the surface ligands of quantum dots to enhance the interfacial bonding force; nano ZrO2 compensates the refractive index difference between quantum dots and the matrix through high refractive index, reduces interfacial light scattering, and at the same time its thermal conductivity improves heat dissipation performance and inhibits quantum dot thermal quenching; fluorine modified polyimide microspheres are uniformly dispersed in the matrix by utilizing its low surface energy to form a hydrophobic barrier to block water and oxygen penetration, and at the same time the fluorine atom electronegativity stabilizes the quantum dot surface defect state to improve the photoluminescence quantum yield; SiO2@TiO2 core-shell light diffuser enhances light scattering through TiO2 shell layer, prolongs the blue light excitation path, and improves the quantum dot conversion efficiency, at the same time the SiO2 core inhibits total reflection to reduce the light output uniformity deviation, and the gradient centrifugation program uses the density difference between ZrO2 and SiO2@TiO2 to form a refractive index gradient distribution under the centrifugal field to realize directional regulation of light and reduce color deviation; UV pre-curing locks the gradient structure by photoinitiated radical polymerization to avoid subsequent thermal curing disturbance, and 150℃ thermal curing promotes complete crosslinking of thiosiloxane to form a three-dimensional network, finally increasing the color gamut and service life of the device.
[0013] PCT / LCP alloy is stamped to form a stepped bowl cup structure, and a magnetron sputtered Ag reflective layer is formed on the inner wall.
[0014] It can be understood that the embodiments of the present application use the low melt viscosity of liquid crystal polymer and the high temperature resistance of PCT to form a stepped bowl cup structure by die stamping under high temperature and high pressure, and the stepped design enhances the light reflection path through geometric optics to improve light capture efficiency; the magnetron sputtered Ag reflective layer uses argon plasma to bombard a silver target to deposit a nanoscale Ag film in a vacuum environment, and the high reflectivity and low dielectric loss of silver form an omnidirectional reflective interface on the inner wall, and at the same time the dense grain structure of silver can reduce light scattering loss and reduce reflectivity deviation.
[0015] An aluminum heat sink adopts a hollow parting grid, the ceramic substrate is embedded in the stepped bowl cup, and 60-70wt% aluminum nitride thiosiloxane glue is filled to form vertical heat conduction and horizontal heat dissipation double channels.
[0016] It can be understood that the embodiment of the application adopts topological optimization design through the hollowed-out parting grid to form porous channels in the aluminum heat sink, which not only reduces the weight but also increases the surface area, and enhances the horizontal direction heat dissipation efficiency through forced convection; the ceramic substrate is embedded into the stepped bowl cup to match the substrate by using the low thermal expansion coefficient of aluminum oxide ceramic, so as to avoid thermal stress cracking, and the stepped structure reduces the light-heat coupling loss through multiple reflections; the aluminum nitride is filled with thioxyl silicone adhesive, a vertical heat conduction path is formed through the high-thermal-conductivity aluminum nitride, the surface is modified by a silane coupling agent, and a chemical bond is formed between the thioxyl silicone matrix, a continuous heat conduction network chain is constructed, the vertical heat conduction coefficient of the composite material is improved, and a double-channel heat flow is formed in the horizontal direction through the aluminum grid heat dissipation.
[0017] The linear driver is welded to the back of the ceramic substrate by using an active metal brazing process.
[0018] It can be understood that the embodiment of the application adopts electromagnetic or piezoelectric driving principle through the linear driver, converts the electrical signal into a micron-level linear displacement through a closed-loop control system, directly acts on the back of the ceramic substrate, and realizes real-time focal length adjustment of the optical element; the ceramic substrate and the low thermal expansion coefficient can quickly conduct the heat generated during the operation of the driver, so as to avoid the influence of thermal deformation on displacement accuracy; the high mechanical strength supports the reaction force of the driver, and ensures the structural stability; the welding adopts an active metal brazing process, a chemical bond is formed through the solder containing Ti / Ag at 800 ℃, the bonding strength is enhanced, and at the same time, the electrical insulation is maintained, so as to prevent the signal interference of the driver on the substrate circuit.
[0019] (8) A 3D direct writing technology is adopted to precisely coat a thioxyl silicone adhesive basic layer outside the Micro-LED chip, the quantum dot optical layer and the electrode structure, and then a 200 nm precision nozzle is used to directly print a super lens array on the surface of the thioxyl silicone adhesive layer.
[0020] It can be understood that the embodiment of the application precisely coats the chip structure by adopting the 3D direct writing technology, the high biocompatibility and low interfacial tension characteristics can seamlessly fit the Micro-LED surface, a chemical bond is formed between the thiol group and the chip electrode, the interfacial stability is improved, and at the same time, the low refractive index reduces the light interface reflection loss; the super lens array printing adopts a 200 nm precision nozzle to spray photosensitive resin ink, the volume and landing accuracy of the droplets are controlled through piezoelectric driving, a periodic micro-nano structure is formed on the surface of the silica gel, the light beam is directionally regulated, the LED light emitting angle is compressed, and the light extraction efficiency is improved; the gradient refractive index design of the super lens can also be cooperatively optimized with the quantum dot layer to optimize the color gamut, and the hydrophobicity and ultraviolet resistance of the silica gel together guarantee the long-term reliability of the device in a humid and hot environment.
[0021] In the step (2), the Sn content in the tin-silver solder paste is 96.5%, and the Ag content is 3.5%.
[0022] The concentration of the cadmium selenide / zinc sulfide quantum dot solution in step (3) is 800-2000 μg / L, the molar concentration of the phosphor doped is 0.115 mol / L, and the thickness is 0.5 mm.
[0023] It can be understood that, by the concentration range of 800-2000 μg / L of the cadmium selenide / zinc sulfide quantum dot solution, the embodiment of the application can ensure uniform distribution of the quantum dots when the capillary force drives filling, while maintaining high fluorescence quantum yield, and the optimization of the molar concentration of 0.115 mol / L of the phosphor doped can balance energy transfer and concentration quenching effect: the rare earth ions form a luminescent center in the thiosiloxane adhesive, and at this concentration, the spacing between the phosphors can achieve efficient energy transfer and avoid efficiency reduction caused by cross relaxation; the design of the thickness of 0.5 mm guarantees blue light absorption rate and reduces light scattering loss.
[0024] The phosphor in step (3) includes KSF:Mn 4+ Red powder and LuAG:Ce 3+ Green powder, KSF:Mn 4+ Red powder: LuAG:Ce 3+ Green powder = 1:1.
[0025] The gradient centrifugation process in step (4) is a slow increase from 0 to 2000 rpm for 2 minutes, and then the speed is increased to 3000 rpm for 3 minutes.
[0026] It can be understood that, by the slow increase, the embodiment of the application can prevent instantaneous settlement or agglomeration of materials (such as nano ZrO2 and fluorine-modified polyimide microspheres) caused by sudden increase of centrifugal force, so as to ensure uniform dispersion of the particles in the thiosiloxane adhesive matrix and gradually form a gradient. During the slow increase process, particles with different densities begin to stratify according to the difference in settlement speed, forming a preliminary refractive index gradient; the high speed of 3000 rpm can enhance the centrifugal field, so that the particles further migrate to the gradient position matched with their density. At this time, ZrO2 with larger density is enriched in the outer layer, while polyimide microspheres with smaller density are gathered in the inner layer, forming a clearer refractive index gradient distribution. The steady state time of 3 minutes balances the separation efficiency and gradient stability; by the segmented control of slow increase-steady state, in combination with the density difference of the materials and the action of the centrifugal field, the precise distribution of the nanoparticles in the quantum dot optical layer is realized.
[0027] The UV pre-curing process in step (4) is a preliminary irradiation of the material by a UV light source with a wavelength of 365 nm for 10 seconds.
[0028] The linear driver in step (7) is Nanximicro NSL21924.
[0029] The height of the superlens in step (7) is 3-5 μm.
[0030] The third aspect of the present application provides an LED lamp strip, which is composed of a transparent conductive substrate, a light-emitting unit, a quantum dot optical layer, a gradient package, a light-heat integrated structure, and an LED lamp bead and patch resistor composed of a driving and optical control, connected by a series-parallel circuit, and covered by a waterproof silicone encapsulation layer and an optical lens.
[0031] Therefore, the present application has at least the following beneficial effects: 1. The present application provides excellent thermal-mechanical stability and high-frequency signal integrity for Micro-LED packaging by using high-purity aluminum oxide substrate with low thermal expansion coefficient and stable dielectric constant, effectively avoiding the problems of substrate warping and electromagnetic signal crosstalk caused by thermal stress. The refractive index of the visible light band and the indium tin oxide film forms a gradient match, significantly reducing the interface reflection loss, and the light extraction efficiency is improved. When depositing the indium tin oxide film by magnetron sputtering, the target material is bombarded by argon plasma, and a precise oxygen control process is introduced to form a dual-function electrode layer with high electrical conductivity and wide spectral transmission. The photolithography process uses 365nm ultraviolet exposure combined with aqua etching, selectively dissolves indium tin oxide through a mask, and forms a micro-electrode array. The anisotropic etching process controls the lateral etching amount within 0.1um, ensuring that the circuit pattern precision reaches the sub-micron level. This design significantly increases the thermal conductivity of the substrate and reduces the thermal resistance. At the same time, the array type die bonding area is arranged by thermal-electricity cooperation, which reduces the chip junction temperature, realizes the unity of high-density integration and high-efficiency heat dissipation, and ensures the stability and life of high-brightness light emission. 2. The present application adopts an electrode face-down structure design for flip-chip Micro-LED chips, and directly soldered with tin-silver solder paste and die bonding area electrode solder joints through high-precision patching process, replacing the traditional gold wire bonding process, shortening the current transmission path and reducing the series resistance. At the same time, the direct heat conduction channel between the solder joint metal and the substrate is used to control the chip junction temperature and improve the heat dissipation efficiency. The inclination adjustment controls the angle between the chip light-emitting surface and the substrate normal to be 15°-30°, optimizes the critical angle of total reflection based on Snell's law, improves the sidewall escape rate of light originally limited inside the material, and improves the light extraction efficiency. Geometrical optics is used to suppress the light crosstalk between adjacent pixels. The micro-channel array forms a capillary channel using deep reactive ion etching process, drives cadmium selenide / zinc sulfide quantum dot solution using surface energy difference, realizes self-filling, and significantly improves filling uniformity. Combined with the limited crystallization effect of ZIF-8 metal organic framework, a 500nm porous protective layer is formed, which reduces the spatial distribution deviation of quantum dots, improves the current injection efficiency, reduces the energy consumption, and improves the light-emitting consistency. 3. The present application realizes precise self-filling of cadmium selenide / zinc sulfide quantum dot solution by using capillary force driving through precisely designed micro-channel array, improves filling uniformity, ensures sub-micron patterned precision of pixel spacing, after spin-coating ZIF-8 metal organic framework precursor, in-situ crystallization forms a regular porous protective layer, the microporous structure of which selectively adsorbs mercaptan ligands on the surface of quantum dots through molecular sieve effect, while the exposed Zn 2+ node forms a strong coordination bond with the sulfur atom in the quantum dot ligand, anchoring the quantum dot in the three-dimensional channel with a position deviation controlled within ±2nm, the refractive index of the porous layer matches the quantum dot, reducing interface light scattering loss and improving visible light transmittance; the subsequently filled thiophenyl siloxane glue forms a support skeleton with high mechanical strength through Si-O-Si crosslinking network, and the doped fluorescent powder is optimized to 10-15nm from the quantum dot, which efficiently converts blue light into green / red light, greatly improving color gamut coverage; the hydrophobic channels of ZIF-8 and the thiophenyl siloxane glue synergistically block water and oxygen permeation, prolonging the life of quantum dots and reducing light decay, further enhancing light conversion efficiency and color purity, effectively inhibiting the oxidation and light decay of quantum dots; 4. The present application provides mechanical support strength through the flexible Si-O-Si crosslinking network of the thiophenyl siloxane glue matrix, while the terminal mercaptan groups form coordination bonds with the surface ligands of the quantum dots, significantly enhancing the interfacial bonding force and reducing quantum dot aggregation; nano ZrO2 effectively matches the refractive index difference between the quantum dots and the matrix by virtue of its high refractive index, reducing interface light scattering loss and accelerating heat diffusion, thereby reducing the thermal quenching rate of the quantum dots; fluorine-modified polyimide microspheres are uniformly dispersed to form a hydrophobic barrier with low water and oxygen permeability, and the strong electronegative fluorine atoms can passivate the sulfur vacancy defects on the surface of the quantum dots, thereby improving the photoluminescence quantum efficiency; SiO2@TiO2 core-shell light diffusion enhances Rayleigh scattering by utilizing the high refractive index of TiO2, thereby lengthening the blue light excitation path and improving quantum dot conversion efficiency, while the SiO2 core reduces the deviation of light uniformity by suppressing total reflection; the gradient centrifugation program forms a refractive index gradient of 0.02 / μm based on the density difference between ZrO2 and SiO2@TiO2, realizing directional regulation of light; UV pre-curing triggers the radical polymerization of thiophenyl siloxane through a photoinitiator, locking the gradient structure within 10 seconds, and subsequent 150℃ thermal curing for 20 minutes promotes complete crosslinking of the siloxane to form a three-dimensional network, ultimately improving the color gamut coverage and prolonging the life of the device; the lens packaging structure expands the viewing angle range through micro-nano surface topography design, and the lens packaging structure enhances the directional regulation ability of light, improving the light uniformity and viewing angle range of the LED; 5.The application is a stepped bowl structure formed by stamping PCT / LCP alloy, which uses the low melt viscosity of LCP and the high temperature resistance of PCT to form a reflective cavity by precise stamping of the mold, which improves the light capture efficiency; the magnetron sputtering Ag reflecting layer uses argon plasma to bombard the pure silver target, which uses the visible light reflectivity and dielectric loss of silver to form an omnidirectional reflection interface, and through the crystal face preferred orientation, the reflectivity deviation is reduced; the hollow parting grid of the aluminum heat sink adopts topological optimization design, the difference in thermal expansion between the aluminum oxide ceramic substrate and the stepped bowl is reduced, avoiding thermal stress cracking, at the same time, the stepped structure reduces the light-heat coupling loss, the thioxyl silicone glue filled with aluminum nitride is modified by silane coupling agent to form Si-O-Al covalent bond, which constructs a continuous network with high vertical thermal conductivity, and cooperates with the horizontal heat dissipation channel of the aluminum grid to form a double-channel heat flow, 3D direct writing technology precisely coats the chip structure, which has high biocompatibility and low interfacial tension characteristics, and can seamlessly fit the Micro-LED surface, forms chemical bonding with the chip electrode through thiol group, improves the interface stability, at the same time, its low refractive index reduces the light interface reflection loss; the super lens array printing uses a 200nm precision nozzle to spray photosensitive resin ink, which controls the droplet volume and landing accuracy through piezoelectric driving, forms a periodic micro-nano structure on the silica gel surface, realizes directional regulation of light beam, compresses the LED light emitting angle, and improves the light extraction efficiency; the gradient refractive index design of the super lens can also be optimized with the quantum dot layer to cooperate with the color gamut, while the hydrophobicity and ultraviolet resistance of the silica gel together guarantee the long-term reliability of the device in a humid and hot environment, further optimize the light beam regulation ability, and realize the LED lamp bead with high brightness, high stability and long service life. BRIEF DESCRIPTION OF DRAWINGS
[0032] The above and / or additional aspects and advantages of the present application will become apparent and more readily appreciated from the following description, taken in conjunction with the following drawings, in which: Figure 1 A process flow chart of a preparation method of an LED lamp bead according to an embodiment of the present application; Figure 2 A heat dissipation double-channel structure schematic diagram of a preparation method of an LED lamp bead according to an embodiment of the present application; Figure 3 A transparent conductive substrate structure schematic diagram of a preparation method of an LED lamp bead according to an embodiment of the present application; Figure 4 A characteristic diagram of the influence of super lens thickness on light extraction efficiency of a preparation method of an LED lamp bead according to an embodiment of the present application; Figure 5 A Micro-LED chip flip-chip structure schematic diagram of a preparation method of an LED lamp bead according to an embodiment of the present application. DETAILED DESCRIPTION
[0033] The technical solutions of the present application are described below through specific examples. It should be understood that the one or more method steps mentioned in the present application do not exclude the existence of other method steps before and after the described combination steps or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these examples are only used to illustrate the present application and not to limit the scope of the present application. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool to identify each method step, and is not a limitation on the arrangement order of each method step or a limitation on the scope of the present application that can be implemented, the change or adjustment of the relative relationship thereof is also considered as the scope of the present application that can be implemented without substantial change of the technical content.
[0034] In order to better understand the above technical solutions, the exemplary embodiments of the present application are described in more detail below. Although exemplary embodiments of the present application are shown, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present application and to fully convey the scope of the present application to those skilled in the art.
[0035] The alumina transparent ceramic substrate used in the embodiments of the present application is from Yangzhou Zhongtianli New Material Co., Ltd.; the indium tin oxide used is from Zhejiang Yame Nanometer Technology Co., Ltd.; the tin-silver solder paste used is from Liyang Ruipu New Material Co., Ltd.; the cadmium selenide used is from Shanghai Aladdin Bio-Chem Technology Co., Ltd.; the zinc sulfide used is from Zhejiang Yame Nanometer Technology Co., Ltd.; the ZIF-8 used is from Shanghai Keshu Chemical Technology Co., Ltd.; the thiosiloxane glue used is from Aibixun Biological Technology Co., Ltd.; the ZrO2 used is from Shanghai Qiantian New Material Technology Co., Ltd.; the fluorine-modified polyimide microspheres used are from Changchun Gaoci Polyimide Material Co., Ltd.; the SiO2@TiO2 used is from Heqing Medical Research Co., Ltd.; the silver used is from Fujian Senxin Material Co., Ltd.; the PCT / LCP alloy used is from Shanghai Plite Composite Material Co., Ltd.; the aluminum nitride used is from Shanghai Maikelin Biochemical Technology Co., Ltd.; the Nanxin Micro NSL21924 used is from Nanxin Microelectronics Co., Ltd.; the Micro-LED chip used is from Sanan Optoelectronics Co., Ltd.
[0036] The following description, with reference to the accompanying drawings, describes an LED lamp bead and its fabrication method, as well as an LED light strip, according to embodiments of this application. Addressing the issues of poor heat dissipation and low luminous efficiency of LED lamp beads mentioned in the background art, this application provides a method for fabricating LED lamp beads. This method utilizes a high-purity alumina substrate with a thermal expansion coefficient matched to that of a Micro-LED chip, combined with an indium tin oxide (ITO) bifunctional electrode layer deposited by magnetron sputtering. Submicron-level circuit patterns are formed through 365nm ultraviolet lithography and aqua regia wet etching, thereby improving the substrate's thermal conductivity and reducing thermal resistance. Simultaneously, interface reflection loss is reduced through refractive index gradient matching. For flip-chip bonding, Sn-Ag eutectic bonding replaces gold wire bonding, reducing series resistance. Light extraction efficiency is improved through tilt angle design. A microchannel array is formed through deep reactive ion etching to create a capillary structure, achieving self-filling of the quantum dot solution. The ZIF-8 porous layer utilizes Zn... 2+ -S coordination bonds fix the quantum dots, and thiosiloxane adhesive constructs a flexible support framework, improving color gamut coverage and extending lifespan. Nano-ZrO2 and SiO2@TiO2 core-shell particles construct a vertical thermally conductive network, and aluminum nitride-filled thiosiloxane adhesive forms Si-O-Al covalent bonds, improving vertical thermal conductivity. PCT / LCP alloy stepped cups and topology-optimized aluminum mesh form a dual-channel heat dissipation system, reducing junction temperature. The superlens array achieves ±15° light emission angle control through 3D printing with a 200nm nozzle. Fluorine-modified polyimide microspheres form a hydrophobic barrier, and combined with UV curing, increase device lifespan in humid and hot environments. The 3D direct-write encapsulation layer chemically bonds to the chip electrodes through thiol groups, improving interfacial shear strength and luminous efficiency. This solves the problems of poor heat dissipation, low luminous efficiency, uneven light emission, and short lifespan of LED chips.
[0037] The following description, with reference to the accompanying drawings, describes an embodiment of an LED lamp bead, its preparation method, and an LED light strip.
[0038] Specifically, Figure 1 This is a schematic flowchart illustrating a method for preparing an LED bead according to an embodiment of this application.
[0039] like Figure 1 As shown, the method for manufacturing this LED bead includes the following steps: In step S101, a high-purity alumina transparent ceramic substrate is selected, an indium tin oxide thin film layer is deposited by magnetron sputtering, a microelectrode circuit is formed by photolithography etching, and an array of die-bonding regions is photolithographically formed on the substrate surface.
[0040] It can be understood that the embodiments of the present application provide thermal-mechanical stability and high-frequency signal integrity by virtue of low thermal expansion coefficient and dielectric constant of high-purity alumina substrate, and the transparency and refractive index of the substrate match the indium tin oxide film to reduce interface light loss. The magnetron sputtering deposition of the indium tin oxide film utilizes argon plasma to bombard an indium tin oxide target, and the carrier concentration is adjusted by oxygen doping to realize low sheet resistance and high light transmittance, thereby providing a conductive-optical dual-functional layer for the electrode. The photolithography and etching use ultraviolet exposure and aqua regia wet etching to selectively dissolve the indium tin oxide, thereby forming microelectrodes with a line width less than 2 μm, and anisotropic etching ensures circuit accuracy; array-type die bonding area photolithography utilizes secondary alignment and oxygen plasma surface activation to enhance the wetting property of the solder paste, thereby providing high-precision positioning and reliable electrical connection for LED chip bonding.
[0041] Specifically, after selecting a high-purity alumina transparent ceramic substrate, first, an indium tin oxide film layer is deposited by magnetron sputtering: in a sputtering chamber with a vacuum degree ≤10 -6 Pa, argon gas is used as the working gas with a flow rate of 100 sccm, a high-purity ITO target is used, the sputtering power is controlled to be 100-300 W, and the substrate temperature is controlled to be 200-300 °C, thereby forming a conductive film with a thickness of 100-200 nm and a visible light transmittance greater than 90%; then, a photolithography process is performed: a photoresist with a thickness of 1-2 μm is spin-coated, 365 nm ultraviolet exposure is combined with a mask pattern, and aqua regia wet etching is used to etch the indium tin oxide layer, with a lateral etching amount controlled to be less than 0.1 μm, thereby forming a microelectrode circuit with submicron precision; finally, an array-type die bonding area is photolithographed on the substrate surface: the same photolithography process is used to define the pad area, and deep reactive ion etching is used to form a microcavity structure with a depth of 5-10 μm, thereby ensuring that the alignment deviation between the die bonding area and the electrode circuit is ≤2 μm, and high-precision thermal-electric collaborative layout is completed.
[0042] In step S102, the flip-chip Micro-LED chip is directly soldered to the die bonding area electrode pad by tin-silver solder paste, and the chip mounting inclination angle is adjusted to 15°-30°.
[0043] In the tin-silver solder paste, the content of Sn is 96.5%, and the content of Ag is 3.5%.
[0044] It can be understood that the flip-chip Micro-LED chip adopts an electrode-down structure, is directly soldered to the die bonding area electrode pad by tin-silver solder paste, omits the traditional gold wire bonding process, shortens the current path and reduces the series resistance, and at the same time, the heat dissipation efficiency is improved by direct contact of the metal pad. The inclination adjustment utilizes the optical reflection principle, calculates the included angle between the chip light emitting surface and the substrate normal line, optimizes the critical angle of total reflection, makes more light escape from the chip sidewall, improves the light extraction efficiency, and reduces the light crosstalk between adjacent pixels.
[0045] Specifically, first, tin-silver solder paste is precisely coated on the die bonding area electrode pad of the alumina substrate by screen printing or dispensing process, with a thickness of 10-20 μm. Then, the flip-chip electrode face is aligned to the pad by using a high-precision chip mounter, and eutectic connection is achieved by hot-press welding, replacing the traditional gold wire bonding, so as to reduce the series resistance. After welding, the chip inclination angle is calibrated by an optical detection system, and the normal angle between the light-emitting surface and the substrate is adjusted to 15°-30° by using a fine adjustment clamp. Based on Snell's law, the critical angle of total reflection is optimized, so as to improve the light escape rate of the side wall. Finally, X-ray detection is used to detect the void rate of the pad, and nitrogen protection cooling is used to avoid electrode cracking caused by thermal stress.
[0046] In step S103, the substrate surface is photoetched with a microchannel array, a cadmium selenide / zinc sulfide quantum dot solution is driven to fill by capillary force, a ZIF-8 metal organic framework precursor is spin-coated, an in-situ crystallization is formed at 150-180°C to form a 500 nm porous protective layer, a thioxyl silicone adhesive doped with fluorescent powder is cured at 150°C for 30 minutes to form a quantum dot optical layer.
[0047] The concentration of the cadmium selenide / zinc sulfide quantum dot solution is 800-2000 μg / L, the molar concentration of the fluorescent powder doped is 0.115 mol / L, and the thickness is 0.5 mm. The fluorescent powder includes KSF:Mn 4+ Red powder and LuAG:Ce 3+ Green powder, KSF:Mn 4+ Red powder: LuAG:Ce 3+ Green powder = 1:1.
[0048] It can be understood that, by using the microchannel array, the cadmium selenide / zinc sulfide quantum dot solution is precisely filled by capillary force in the embodiments of the application, so as to ensure pixelization uniformity. After the ZIF-8 metal organic framework precursor is spin-coated, an in-situ crystallization is formed at 150-180°C to form a 500 nm porous protective layer, the pore diameter of which is 2-3 nm and can selectively adsorb quantum dot surface ligands. Through the coordination of Zn 2+ The coordination of the quantum dot thiol ligand stabilizes the quantum dot position, while the porous structure reduces light scattering loss and improves light transmittance. After the thioxyl silicone adhesive doped with fluorescent powder is cured, a composite optical layer is formed, the crosslinked network Si-O-Si bond of which provides mechanical support, and the fluorescent powder and the quantum dots cooperatively emit light. Through the resonance energy transfer of the Foster principle, blue light is converted into green / red light, so as to provide color gamut coverage. The hydrophobicity of ZIF-8 blocks water and oxygen penetration, so as to prolong the life of the quantum dots.
[0049] Specifically, a microfluidic array is formed on the substrate surface by deep reactive ion etching, a cadmium selenide / zinc sulfide quantum dot solution is driven to fill into the microcavity by capillary force, the positioning accuracy is ±2 nm, then a ZIF-8 precursor solution is spin-coated, and the ZIF-8 is crystallized in situ at 150 ℃ for 2 hours to form a porous protective layer with a pore size of 0.5 nm and a thickness of 500 nm, and then Zn 2+ The quantum dots are fixed by coordination bonding with thiol ligands on the surface of the quantum dots, and then a thiosiloxane adhesive doped with fluorescent powder is coated, the Si-O-Si crosslinking network of the thiosiloxane adhesive cooperates with the ZIF-8 channel to block water and oxygen, and finally a quantum dot optical layer is formed by heat curing at 150 ℃ for 30 minutes, the color gamut coverage is improved, and the light decay is reduced.
[0050] In step S104, the thiosiloxane adhesive is used as a matrix, 8-12 wt% nano ZrO2 and 4-8 wt% fluorine-modified polyimide microspheres are doped, and 2-4 wt% SiO2@TiO2 core-shell light diffuser is added, vacuum degassing is performed after mixing, degassing is performed for 5 minutes at-0.1 MPa, the lens mold is injected, and a refractive index gradient is formed by a gradient centrifugation process, then UV pre-curing is performed to lock the gradient distribution, and finally heat curing at 150 ℃ for 20 minutes completes the packaging of the quantum dot optical layer.
[0051] The gradient centrifugation process is a 2-minute slow rise from 0 to 2000 rpm, and then the speed is raised to 3000 rpm for 3 minutes of stable state The UV pre-curing process is a preliminary irradiation of 10 seconds on the material by using a UV light source with a wavelength of 365 nm.
[0052] It can be understood that the embodiments of the present application provide mechanical support by the flexible Si-O-Si network structure of the thiosiloxane adhesive matrix, and the thiol groups of the thiosiloxane adhesive can form coordination bonds with the surface ligands of the quantum dots to enhance the interfacial bonding force; the nano ZrO2 compensates for the refractive index difference between the quantum dots and the matrix by high refractive index, reduces the interfacial light scattering, and improves the heat dissipation performance by the thermal conductivity to inhibit the thermal quenching of the quantum dots; the fluorine-modified polyimide microspheres are uniformly dispersed in the matrix to form a hydrophobic barrier to block the penetration of water and oxygen, and the electronegativity of the fluorine atom stabilizes the surface defect state of the quantum dots to improve the photoluminescence quantum yield; the SiO2@TiO2 core-shell light diffuser enhances light scattering by the TiO2 shell to prolong the blue light excitation path and improve the quantum dot conversion efficiency, while the SiO2 core inhibits total reflection to reduce the uniformity deviation of light emission; the gradient centrifugation process forms a refractive index gradient distribution under the centrifugal field by the density difference between ZrO2 and SiO2@TiO2 to realize directional regulation of light and reduce color deviation; the UV pre-curing locks the gradient structure by photoinitiated radical polymerization to avoid disturbance of subsequent heat curing, and the heat curing at 150 ℃ promotes complete crosslinking of the thiosiloxane to form a three-dimensional network, finally improving the color gamut and increasing the service life of the device.
[0053] Specifically, the thiosiloxane glue is mixed with 8wt% nano Zr02, 5wt% fluorine modified polyimide microspheres and 2wt% Si02@Ti02core-shell light diffuser, and is uniformly dispersed by planetary stirring at a speed of 2000 rpm for 30 minutes. Then, the mixture is degassed for 5 minutes under a vacuum environment of -0.1 MPa to eliminate micro-bubbles. Subsequently, the mixture is injected into a preheated lens mold, and a gradient centrifugal program is adopted to form a refractive index gradient distribution of 0.02 / μm at a speed of 500-3000 rpm for 10 minutes. The density difference between Zr02and Si02@Ti02is used to realize light directional regulation. UV pre-curing is immediately performed at a wavelength of 365 nm, an intensity of 50 mW / cm 2 for 10 seconds to lock the gradient structure. Finally, thermal curing is performed at 150°C for 20 minutes to promote complete cross-linking of the siloxane to form a three-dimensional network, so that the quantum dot optical layer has high light transmittance, low water and oxygen permeability and excellent thermal stability.
[0054] In step S105, the PCT / LCP alloy is stamped to form a stepped bowl cup structure, and an Ag reflective layer is magnetron sputtered on the inner wall.
[0055] It can be understood that, by stamping the PCT / LCP alloy, the low melt viscosity of the liquid crystal polymer and the high temperature resistance of the PCT are utilized to form a stepped bowl cup structure under high temperature and high pressure through a mold. The stepped design enhances the multiple reflection path of light through geometric optics principles, and improves the light capture efficiency. The magnetron sputtering Ag reflective layer uses argon plasma to bombard a silver target to deposit a nanoscale Ag film in a vacuum environment. The high reflectivity and low dielectric loss of silver enable the inner wall to form an omnidirectional reflective interface, and the dense grain structure of silver can reduce light scattering loss and reduce reflectivity deviation.
[0056] Specifically, first, the PCT / LCP alloy plate is placed in a precision progressive die, and blanking, deep drawing and stepped forming are sequentially completed by a multi-station stamping equipment: a two-stage deep drawing process is adopted to form a stepped bowl cup structure, the round corner radius of the punch and the blank holder force are controlled to avoid material wrinkling or breaking, and hot stamping is performed at 150-180°C to reduce residual stress. Subsequently, the Ag reflective layer is magnetron sputtered on the inner wall of the bowl cup: in a vacuum chamber with a pressure of 0.1-0.5 Pa, a high-purity Ag target is used as a source, a bias voltage of 300-500 V and a power density of 5-10 W / cm 2 are applied, Ag atoms are deposited to form a dense reflective layer with a thickness of 200-500 nm by Ar ion bombardment. During the sputtering process, the workpiece holder is rotated at a speed of 5-15 rpm to ensure the uniformity of the film layer. Finally, annealing is performed at 150°C for 2 hours to eliminate internal stress and improve the adhesion of the Ag layer.
[0057] In step S106, the aluminum heat sink adopts a hollow parting grid, the ceramic substrate is embedded in a stepped bowl cup, and 60-70wt% aluminum nitride is filled with a thioxyl silicone glue to form a vertical heat conduction and horizontal heat dissipation double channel.
[0058] It can be understood that the embodiment of the application adopts topological optimization design through the hollow parting grid to form a porous channel in the aluminum heat sink, which not only reduces the weight but also increases the surface area, and enhances the horizontal direction heat dissipation efficiency through forced convection; the ceramic substrate is embedded in the stepped bowl cup to match the substrate by using the low thermal expansion coefficient of aluminum oxide ceramic, thereby avoiding thermal stress cracking, and the stepped structure reduces the light-heat coupling loss through multiple reflections; the aluminum nitride is filled with a thioxyl silicone glue, a vertical heat conduction path is formed through the high-thermal-conductivity aluminum nitride, the surface is modified by a silane coupling agent to form a chemical bond with the thioxyl silicone matrix, a continuous heat conduction network chain is constructed, the vertical heat conduction coefficient of the composite material is improved, and a double-channel heat flow is formed through the aluminum grid heat dissipation in the horizontal direction.
[0059] Specifically, the hollow parting grid is processed on the aluminum heat sink body by precise milling or laser cutting, then the pre-prepared PCT / LCP alloy stepped bowl cup structure is embedded in the grid reserved cavity, the metal-ceramic interface is tightly attached through a hot pressing process at a temperature of 180-200℃ and a pressure of 5-10MPa; then 60wt% aluminum nitride modified thioxyl silicone glue is filled, vacuum injection is adopted to ensure that the glue completely penetrates the grid pores, and gradient centrifugation is adopted to make the aluminum nitride particles gradiently distributed in the vertical direction, thereby forming a vertical directional heat conduction channel, finally 150℃ solidification for 20 minutes is adopted, so that the aluminum alloy grid in the horizontal direction and the vertical aluminum nitride glue layer constitute a double-channel heat dissipation structure, thereby reducing the temperature difference.
[0060] In step S107, the back surface of the ceramic substrate is welded with a linear driver by an active metal brazing process.
[0061] The linear driver is of Nanxie micro NSL21924 type, and the super lens height is 3-5μm.
[0062] It can be understood that the embodiment of the application adopts electromagnetic or piezoelectric driving principle through the linear driver, converts the electrical signal into a micron-level linear displacement through a closed-loop control system, directly acts on the back surface of the ceramic substrate, realizes real-time focal length adjustment of the optical element, the ceramic substrate and the low thermal expansion coefficient can quickly lead out the heat generated during the operation of the driver, thereby avoiding the influence of thermal deformation on displacement accuracy, the high mechanical strength supports the reaction force of the driver, and ensures the structural stability; the welding adopts an active metal brazing process, a chemical bond is formed at 800℃ through the solder containing Ti / Ag, the bonding strength is enhanced, and the electrical insulation is maintained at the same time, thereby preventing the signal interference of the driver to the substrate circuit.
[0063] Specifically, when welding the linear driver to the back of the ceramic substrate by the active metal brazing process, first, the ceramic substrate and the oxygen-free copper foil are surface treated, and the oil stains and oxide layers are removed by ultrasonic cleaning to ensure the surface cleanliness. Then, the active brazing filler is uniformly coated on the back of the ceramic by the thick film screen printing process, with the thickness controlled at 25-40 μm, and dried to remove the solvent. The copper connecting end of the linear driver is aligned and assembled with the ceramic substrate, and then placed in a vacuum brazing furnace after clamping. The temperature is raised to 780-840 ℃ at a rate of 10-15 ℃ / min under a vacuum environment of 5×10 -3 Pa, and kept for 3-5 minutes to make the brazing filler melt and react with the ceramic to form a transition layer such as TiN / TiC, so as to realize metallurgical bonding. Then, the temperature is slowly cooled to below 300 ℃ at a rate of 5 ℃ / min to avoid thermal stress cracking, and finally a reliable connection with high thermal conductivity and large shear strength is formed.
[0064] In step S108, a 3D direct writing technology is used to precisely coat a thiyl siloxane glue basic layer outside the Micro-LED chip, quantum dot optical layer and electrode structure, and then a 200 nm precision nozzle is used to directly print a super lens array on the surface of the thiyl siloxane glue layer.
[0065] It can be understood that the embodiments of the present application precisely coat the chip structure by using the 3D direct writing technology, which has high biocompatibility and low interfacial tension characteristics and can seamlessly fit the Micro-LED surface. The thiol group forms a chemical bond with the chip electrode to improve the interfacial stability, and the low refractive index reduces the light interface reflection loss. The super lens array printing uses a 200 nm precision nozzle to spray photosensitive resin ink, and the drop volume and landing accuracy are controlled by piezoelectric driving to form a periodic micro-nano structure on the surface of the silica gel, realize light beam directional regulation, compress the LED light output angle, and improve the light extraction efficiency. The gradient refractive index design of the super lens can also be optimized in cooperation with the quantum dot layer to improve the color gamut, and the hydrophobicity and ultraviolet resistance of the silica gel together guarantee the long-term reliability of the device in a humid and hot environment.
[0066] Specifically, a 3D direct writing technology is used to coat a thiyl siloxane glue basic layer outside the Micro-LED chip, quantum dot layer and electrode structure, to realize uniform coating without bubbles through air pressure control and path planning, and to lock the structure by pre-curing for 10 seconds under a nitrogen environment with 365 nm ultraviolet light. Then, a 200 nm precision nozzle is used to print TiO2 nanoparticle ink on the surface of the silica gel layer, with a 10 nm / 20 nm mixed ratio of 1:1 and a solid content of 30%. The super lens array unit with a height of 5 μm and a period of 600 nm is formed by point-by-point stacking. After printing, the device is heat treated at 150 ℃ to remove organic solvents, and then a thiyl siloxane glue film is deposited on the surface of the lens by atomic layer deposition to improve the refractive index.
[0067] This application provides a method for fabricating LED chips. It utilizes a high-purity alumina substrate with a thermal expansion coefficient matched to that of a Micro-LED chip, combined with an indium tin oxide (ITO) bifunctional electrode layer deposited by magnetron sputtering. Submicron-level circuit patterns are formed through 365nm ultraviolet lithography and aqua regia wet etching, thereby improving the substrate's thermal conductivity and reducing thermal resistance. Simultaneously, interface reflection loss is reduced through refractive index gradient matching. For flip-chip bonding, Sn-Ag eutectic bonding replaces gold wire bonding, reducing series resistance. Light extraction efficiency is improved through tilt angle design. A microchannel array is formed through deep reactive ion etching to create a capillary structure, achieving self-filling of the quantum dot solution. The ZIF-8 porous layer utilizes Zn... 2+ -S coordination bonds fix the quantum dots, and thiosiloxane adhesive constructs a flexible support framework, improving color gamut coverage and extending lifespan. Nano-ZrO2 and SiO2@TiO2 core-shell particles construct a vertical thermally conductive network, and aluminum nitride-filled thiosiloxane adhesive forms Si-O-Al covalent bonds, improving vertical thermal conductivity. PCT / LCP alloy stepped cups and topology-optimized aluminum mesh form a dual-channel heat dissipation system, reducing junction temperature. A superlens array is 3D printed with a 200nm nozzle to achieve a 15° light emission angle control. Fluorine-modified polyimide microspheres form a hydrophobic barrier, and combined with UV curing, increase device lifespan in humid and hot environments. The 3D direct-write encapsulation layer chemically bonds to the chip electrodes through thiol groups, improving interfacial shear strength and luminous efficiency. This solves the problems of poor heat dissipation, low luminous efficiency, uneven light emission, and short lifespan of LED chips.
[0068] The following will describe a method for preparing an LED chip according to this application through specific embodiments, including: Example 1: This application proposes an LED lamp bead, which consists of a transparent conductive substrate, a light-emitting unit, a quantum dot optical layer, a gradient package, a photothermal integrated structure, and driving and optical control.
[0069] This application also provides a method for preparing LED beads, including the following steps: (1) A high-purity alumina transparent ceramic substrate is selected, an indium tin oxide thin film layer is deposited by magnetron sputtering, a microelectrode circuit is formed by photolithography etching, and an array of die-bonding areas is photolithographically formed on the substrate surface. (2) Use flip-chip Micro-LEDs and solder them directly to the die bond electrode joints using tin-silver solder paste, adjusting the chip mounting angle to 15°; (3) Photolithographic microchannel array on substrate surface, capillary force driven filling of cadmium selenide / zinc sulfide quantum dot solution, spin coating of ZIF-8 metal-organic framework precursor, in-situ crystallization at 150℃ to form a 300nm porous protective layer, covering with phosphor-doped thiosiloxane adhesive, curing at 150℃ for 30 minutes to form quantum dot optical layer. (4) Adopting thiosiloxane glue as the matrix, doping 8wt% nano ZrO2 and 4wt% fluorine modified polyimide microspheres, adding 2wt% SiO2@TiO2 core-shell light diffuser, mixing and vacuum degassing, degassing for 5 minutes under -0.1MPa, injecting into the lens mold and forming the refractive index gradient by gradient centrifugation, then performing UV pre-curing to lock the gradient distribution, and then performing 150℃ heat curing for 20 minutes to complete the encapsulation of the quantum dot optical layer; (5) Punching PCT / LCP alloy to form a stepped bowl cup structure, and magnetron sputtering Ag reflective layer on the inner wall; (6) The aluminum heat sink adopts a hollow split grid, the ceramic substrate is embedded in the stepped bowl cup, and 60wt% aluminum nitride thiosiloxane glue is filled to form a vertical heat conduction and horizontal heat dissipation double channel; (7) The back of the ceramic substrate is welded with a linear driver by active metal brazing process; (8) Adopting 3D direct writing technology to precisely coat a thiosiloxane glue base layer outside the Micro-LED chip, quantum dot optical layer and electrode structure, and then directly printing a super lens array on the surface of the thiosiloxane glue layer through a 200nm precision nozzle.
[0070] Among them, the tin content in the tin-silver solder paste in step (2) is 96.5%, and the silver content is 3.5%.
[0071] Among them, the concentration of cadmium selenide / zinc sulfide quantum dot solution in step (3) is 800μg / L, the molar concentration of phosphor doping is 0.115mol / L, and the thickness is 0.5mm.
[0072] Among them, the phosphor in step (3) includes KSF:Mn 4+ Red powder and LuAG:Ce 3+ Green powder, KSF:Mn 4+ Red powder: LuAG:Ce 3+ Green powder = 1:1, KSF:Mn 4+ Red powder: LuAG:Ce 3+ Green powder = 1:1.
[0073] Among them, the gradient centrifugation process in step (4) is 0 to 2000rpm for 2 minutes, and then the speed is increased to 3000rpm for 3 minutes.
[0074] Among them, the UV pre-curing process in step (4) is to use a 365nm ultraviolet light source to preliminarily irradiate the material for 10 seconds.
[0075] Among them, the linear driver in step (7) is Nanxin Micro NSL21924.
[0076] Among them, the super lens height in step (7) is 3μm.
[0077] The LED lamp bead of Example 1 is obtained, color gamut coverage is calculated by CIE1931, light extraction efficiency is calculated by comparing the internally generated light power and the actual output light power, the temperature change curve with time is recorded by applying a short power pulse, the thermal resistance distribution is analyzed by using the structure function, the accelerated aging test is carried out synchronously, the light decay rate is measured after 1000 hours of continuous work under constant current driving, and the service life is calculated, so as to obtain the specific performance parameters of the LED lamp bead of Example 1, and the comparison of the numerical value with the typical value range of the industry is shown in Table 1: Table 1: Comparison of numerical value of LED lamp bead of Example 1 with typical value range of industry Index Example 1 LED lamp bead value Ordinary LED lamp bead Luminous efficiency 200 lm / W < 120 lm / W Light decay rate 5% / 1000 hours > 20% / 1000 hours Service life 80,000 hours 20,000 hours Color gamut coverage NTSC 120% NTSC 70-85% Thermal resistance 2K / W > 5K / W Drive response 1 μs > 10 μs Light extraction efficiency 92% 60-70% As shown in Table 1, high-purity alumina transparent ceramic substrate is selected, indium tin oxide film layer is deposited by magnetron sputtering, microelectrode circuit is formed by photolithography and etching, thermal resistance is reduced, flip-chip Micro-LED chip is directly soldered to the die bonding area through tin-silver solder paste, 15° inclination installation and Ag reflection layer are combined, and interface light loss is reduced, light extraction efficiency is improved, 60-70wt% aluminum nitride glue is filled in the aluminum hollow grid, PCT / LCP alloy step bowl cup is used for cooperative heat dissipation, light attenuation is reduced, service life is increased, and nanometer core micro NSL21924 linear driver is used, and driving response time is reduced.
[0078] The application also provides an LED lamp strip, the LED lamp strip is composed of an LED lamp bead and a patch resistor, the LED lamp bead is composed of a transparent conductive substrate, a light-emitting unit, a quantum dot optical layer, a gradient encapsulation body, a light-heat integrated structure, and a driving and optical regulation, and the LED lamp bead and the patch resistor are connected through a series-parallel circuit and covered by a waterproof silicone encapsulation layer and an optical lens.
[0079] Example 2: The application provides an LED lamp bead, the LED lamp bead is composed of a transparent conductive substrate, a light-emitting unit, a quantum dot optical layer, a gradient encapsulation body, a light-heat integrated structure, and a driving and optical regulation.
[0080] The application also provides a preparation method of the LED lamp bead, including the following steps: (1) high-purity alumina transparent ceramic substrate is selected, indium tin oxide film layer is deposited by magnetron sputtering, microelectrode circuit is formed by photolithography and etching, and array type die bonding area is photolithographed on the surface of the substrate; (2) flip-chip Micro-LED chip is used, tin-silver solder paste is directly soldered to the electrode soldering point of the die bonding area, and the inclination angle of the chip installation is adjusted to 18°; (3) The substrate surface is photoetched with a microchannel array, the capillary force drives the filling of cadmium selenide / zinc sulfide quantum dot solution, spin-coating ZIF-8 metal organic framework precursor, in-situ crystallization at 160°C to form a 400 nm porous protective layer, covering the doped fluorescent powder with a thiokol adhesive, curing at 150°C for 30 minutes to form a quantum dot optical layer; (4) The thiokol adhesive is used as a matrix, doped with 10wt% nano ZrO2 and 5wt% fluorine-modified polyimide microspheres, and 3wt% SiO2@TiO2 core-shell light diffuser is added, mixed and vacuum degassed, degassed at-0.1 MPa for 5 minutes, injected into the lens mold and formed into a refractive index gradient by gradient centrifugation, then UV pre-cured to lock the gradient distribution, and finally heat cured at 150°C for 20 minutes to complete the packaging of the quantum dot optical layer; (5) The PCT / LCP alloy is punched to form a stepped bowl cup structure, and the inner wall is magnetron sputtered with an Ag reflective layer; (6) The aluminum heat sink adopts a hollow dividing grid, the ceramic substrate is embedded in the stepped bowl cup, and the thiokol adhesive filled with 60wt% aluminum nitride is formed to form a vertical heat conduction and horizontal heat dissipation double channel, as shown in Figure 2 ; (7) The back of the ceramic substrate is welded with a linear driver by active metal brazing process; (8) The 3D direct writing technology is used to precisely coat the thiokol adhesive basic layer outside the Micro-LED chip, quantum dot optical layer and electrode structure, and then the 200 nm precision nozzle is used to directly print the super lens array on the surface of the thiokol adhesive layer.
[0081] In step (2), the Sn content in the tin-silver solder paste is 96.5%, and the Ag content is 3.5%.
[0082] In step (3), the concentration of cadmium selenide / zinc sulfide quantum dot solution is 800 μg / L, the molar concentration of fluorescent powder doping is 0.115 mol / L, and the thickness is 0.5 mm.
[0083] In step (3), the fluorescent powder includes KSF:Mn 4+ red powder and LuAG:Ce 3+ green powder, KSF:Mn 4+ red powder: LuAG:Ce 3+ green powder = 1:1, KSF:Mn 4+ red powder: LuAG:Ce 3+ green powder = 1:1.
[0084] In step (4), the gradient centrifugation process is 0 to 2000 rpm for 2 minutes, and then the speed is increased to 3000 rpm for 3 minutes.
[0085] In step (4), the UV pre-curing process involves using a 365nm ultraviolet light source to irradiate the material for 10 seconds.
[0086] In step (7), the linear driver model is Nanochip NSL21924.
[0087] In step (7), the height of the superlens is 4 μm.
[0088] The LED beads of Example 2 were used to calculate the color gamut coverage using CIE1931. Simultaneously, the light extraction efficiency was calculated by comparing the internally generated light power with the actual output light power. Short-duration power pulses were applied, and the temperature change curve over time was recorded. Thermal resistance distribution was analyzed using structure functions. Accelerated aging tests were conducted concurrently. After 1000 hours of continuous operation under constant current drive, the light decay rate was measured, and the lifespan was estimated. The specific performance parameters of the LED beads of Example 2 were thus obtained. A comparison of these values with typical industry values is shown in Table 2. Table 2: Comparison of LED chip values in Example 2 with typical industry values. Index Example 2 LED lamp bead value Ordinary LED lamp bead Luminous efficiency 210 lm / W < 120 lm / W Light decay rate 4% / 1000 hours > 20% / 1000 hours Service life 100,000 hours 20,000 hours Color gamut coverage NTSC 126% NTSC 70-85% Thermal resistance 1.8K / W > 5K / W Drive response 1 μs > 10 μs Light extraction efficiency 93% 60-70% Compared to Example 1, Example 2 features an increased chip mounting angle, increased in-situ crystallization temperature, reduced light decay rate, and improved luminous efficiency, along with nano-ZrO. 2、 The addition of fluorine-modified polyimide microspheres and SiO2@TiO2 increases the light extraction efficiency and service life.
[0089] This application also proposes an LED light strip, which consists of a transparent conductive substrate, a light-emitting unit, a quantum dot optical layer, a gradient encapsulation body, a photothermal integrated structure, and LED beads and chip resistors composed of driving and optical control, connected by a series and parallel circuit, and covered with a waterproof silicone encapsulation layer and an optical lens.
[0090] Example 3: This application proposes an LED lamp bead, which consists of a transparent conductive substrate, a light-emitting unit, a quantum dot optical layer, a gradient package, a photothermal integrated structure, and a driving and optical control mechanism.
[0091] This application also provides a method for preparing LED beads, including the following steps: (1) A high-purity alumina transparent ceramic substrate is selected, an indium tin oxide thin film layer is deposited by magnetron sputtering, and a microelectrode circuit is formed by photolithography etching. An array of die-bonding regions is then photolithographically formed on the substrate surface, such as... Figure 3 As shown; (2) A flip-chip Micro-LED is used and directly soldered to the die bond electrode joint using tin-silver solder paste, with the chip mounting tilt angle adjusted to 22°. (3) The substrate surface is photoetched with a microchannel array, the capillary force drives the filling of cadmium selenide / zinc sulfide quantum dot solution, spin coating ZIF-8 metal organic framework precursor, in-situ crystallization at 160°C to form a 400 nm porous protective layer, covering the doped fluorescent powder with a thiokol adhesive, curing at 150°C for 30 minutes to form a quantum dot optical layer; (4) The thiokol adhesive is used as a matrix, doped with 10wt% nano ZrO2 and 6wt% fluorine modified polyimide microspheres, and 3wt% SiO2@TiO2 core-shell light diffuser is added, mixed and vacuum degassed, degassed for 5 minutes at-0.1 MPa, injected into the lens mold and formed into a refractive index gradient by gradient centrifugation, then UV pre-cured to lock the gradient distribution, and then heat cured at 150°C for 20 minutes to complete the packaging of the quantum dot optical layer; (5) The PCT / LCP alloy is punched to form a stepped bowl cup structure, and the inner wall is magnetron sputtered with an Ag reflective layer; (6) The aluminum heat sink adopts a hollow split grid, the ceramic substrate is embedded in the stepped bowl cup, and the thiokol adhesive filled with 70wt% aluminum nitride is formed into a vertical heat conduction and horizontal heat dissipation double channel; (7) The back of the ceramic substrate is welded with a linear driver by active metal brazing process; (8) The 3D direct writing technology is used to precisely coat the thiokol adhesive basic layer outside the Micro-LED chip, quantum dot optical layer and electrode structure, and then the 200nm precision nozzle is used to directly print the super lens array on the surface of the thiokol adhesive layer.
[0092] In step (2), the Sn content in the tin-silver solder paste is 96.5%, and the Ag content is 3.5%.
[0093] In step (3), the concentration of cadmium selenide / zinc sulfide quantum dot solution is 1400 μg / L, the molar concentration of fluorescent powder doping is 0.115 mol / L, and the thickness is 0.5 mm.
[0094] In step (3), the fluorescent powder includes KSF:Mn 4+ Red powder and LuAG:Ce 3+ Green powder, KSF:Mn 4+ Red powder: LuAG:Ce 3+ Green powder = 1:1, KSF:Mn 4+ Red powder: LuAG:Ce 3+ Green powder = 1:1.
[0095] In step (4), the gradient centrifugation process is 0 to 2000 rpm for 2 minutes, and then the speed is increased to 3000 rpm for 3 minutes.
[0096] Wherein, step (4) UV pre-curing process is to use a wavelength of 365 nm UV light source for 10 seconds of preliminary irradiation.
[0097] Wherein, step (7) linear driver model is Nanximicro NSL21924.
[0098] Wherein, step (7) superlens height is 4 μm.
[0099] The LED lamp bead of example 3 is obtained. The color gamut coverage is calculated by CIE1931, the light extraction efficiency is calculated by comparing the internally generated light power with the actual output light power, the temperature change curve with time is recorded by applying a short power pulse, the thermal resistance distribution is analyzed by using the structure function, the accelerated aging test is carried out synchronously, the light decay rate is measured after working for 1000 hours under constant current driving, and the service life is calculated, so that the specific performance parameters of the LED lamp bead of example 3 are obtained. The numerical values are compared with the typical value range of the industry, as shown in table 3: Table 3: comparison of numerical values of LED lamp bead of example 3 with typical value range of industry Index Example 3 LED lamp bead value Ordinary LED lamp bead Luminous efficiency 220 lm / W < 120 lm / W Light decay rate 3% / 1000 hours > 20% / 1000 hours Service life 130,000 hours 20,000 hours Color gamut coverage NTSC 128% NTSC 70-85% Thermal resistance 1.5K / W > 5K / W Drive response 1 μs > 10 μs Light extraction efficiency 94% 60-70% Compared with example 2, the chip mounting inclination angle of example 3 is further increased, the luminous efficiency is improved, the filling amount of aluminum nitride is increased, the concentration of cadmium selenide / zinc sulfide quantum dot solution is increased, so that the color gamut coverage is increased, and the thermal resistance is reduced.
[0100] The application also provides an LED lamp strip. The LED lamp strip is composed of a transparent conductive substrate, a light-emitting unit, a quantum dot optical layer, a gradient encapsulation body, a light-heat integrated structure, and an LED lamp bead and a patch resistor composed of a driving and optical regulation.
[0101] Example 4: The application provides an LED lamp bead. The LED lamp bead is composed of a transparent conductive substrate, a light-emitting unit, a quantum dot optical layer, a gradient encapsulation body, a light-heat integrated structure, and a driving and optical regulation.
[0102] The application also provides a preparation method of an LED lamp bead, including the following steps: (1) a high-purity aluminum oxide transparent ceramic substrate is selected, an indium tin oxide film layer is deposited by magnetron sputtering, a microelectrode circuit is formed by photolithography and etching, and an array type die bonding area is formed on the surface of the substrate; (2) a flip-chip Micro-LED chip is used, and the chip is directly welded to the electrode welding point of the die bonding area through tin-silver solder paste. The chip mounting inclination angle is adjusted to 22°. (3) The substrate surface is photoetched with a microchannel array, the capillary force drives the filling of cadmium selenide / zinc sulfide quantum dot solution, spin coating ZIF-8 metal organic framework precursor, in-situ crystallization at 180°C to form a 500nm porous protective layer, covering the doped fluorescent powder with a thiokol adhesive, curing at 150°C for 30 minutes to form a quantum dot optical layer; (4) The thiokol adhesive is used as a matrix, doped with 12wt% nano ZrO2 and 8wt% fluorine modified polyimide microspheres, and 3wt% SiO2@TiO2 core-shell light diffuser is added, mixed and vacuum degassed, degassed for 5 minutes at-0.1MPa, injected into the lens mold and formed into a refractive index gradient by gradient centrifugation, then UV pre-cured to lock the gradient distribution, and finally heat cured at 150°C for 20 minutes to complete the packaging of the quantum dot optical layer; (5) The PCT / LCP alloy is punched to form a stepped bowl cup structure, and the inner wall is magnetron sputtered with an Ag reflective layer; (6) The aluminum heat sink adopts a hollow split grid, the ceramic substrate is embedded in the stepped bowl cup, and the thiokol adhesive filled with 70wt% aluminum nitride is formed into a vertical heat conduction and horizontal heat dissipation double channel; (7) The back of the ceramic substrate is welded with a linear driver by active metal brazing process; (8) The 3D direct writing technology is used to precisely coat the thiokol adhesive basic layer outside the Micro-LED chip, quantum dot optical layer and electrode structure, and then the 200nm precision nozzle is used to directly print the super lens array on the surface of the thiokol adhesive layer.
[0103] In step (2), the Sn content in the tin-silver solder paste is 96.5%, and the Ag content is 3.5%.
[0104] In step (3), the concentration of cadmium selenide / zinc sulfide quantum dot solution is 1400μg / L, the molar concentration of fluorescent powder doping is 0.115mol / L, and the thickness is 0.5mm.
[0105] In step (3), the fluorescent powder includes KSF:Mn 4+ Red powder and LuAG:Ce 3+ Green powder, KSF:Mn 4+ Red powder: LuAG:Ce 3+ Green powder = 1:1, KSF:Mn 4+ Red powder: LuAG:Ce 3+ Green powder = 1:1.
[0106] In step (4), the gradient centrifugation process is 0 to 2000rpm for 2 minutes, and then the speed is increased to 3000rpm for 3 minutes.
[0107] Wherein, step (4) UV pre-curing process is to use a wavelength of 365 nm UV light source to the material for 10 seconds of preliminary irradiation.
[0108] Wherein, step (7) linear driver model is Nanximicro NSL21924.
[0109] Wherein, step (7) superlens height is 4um, as shown in Figure 4 .
[0110] The LED lamp bead of example 4 is calculated by CIE1931 to obtain the color gamut coverage rate, and the light extraction efficiency is calculated by comparing the internally generated light power with the actual output light power, the temperature change curve with time is recorded by applying a short power pulse, the thermal resistance distribution is analyzed by using the structure function, the accelerated aging test is carried out synchronously, the light decay rate is measured after working for 1000 hours under constant current driving, and the service life is calculated, so as to obtain the specific performance parameters of the LED lamp bead of example 4, and the comparison of the numerical value with the typical value range of the industry is shown in table 4: Table 4: comparison of numerical value of LED lamp bead of example 4 with typical value range of industry Index Example 4 LED lamp bead value Ordinary LED lamp bead Luminous efficiency 225 lm / W < 120 lm / W Light decay rate 2% / 1000 hours > 20% / 1000 hours Service life 140,000 hours 20,000 hours Color gamut coverage NTSC 132% NTSC 70-85% Thermal resistance 1.4K / W > 5K / W Drive response 1 μs > 10 μs Light extraction efficiency 95% 60-70% Compared with example 3, example 4 improves the in-situ crystallization temperature, increases the luminous efficiency, reduces the light attenuation, and increases the service life of nanometer ZrO 2、 The color gamut coverage rate increases, the thermal resistance decreases, and the service life increases with the increase of the amount of fluorine modified polyimide microspheres and the concentration of cadmium selenide / zinc sulfide quantum dot solution.
[0111] The application also provides an LED lamp strip, which comprises an LED lamp bead and a patch resistor, and is connected through a series-parallel circuit and covered by a waterproof silicone encapsulation layer and an optical lens.
[0112] Example 5: The application provides an LED lamp bead, which comprises a transparent conductive substrate, a light emitting unit, a quantum dot optical layer, a gradient encapsulation body, a light-heat integrated structure and driving and optical regulation.
[0113] The application also provides a preparation method of the LED lamp bead, which comprises the following steps: (1) a high-purity alumina transparent ceramic substrate is selected, an indium tin oxide film layer is deposited by magnetron sputtering, a microelectrode circuit is formed by photolithography and etching, and an array type die bonding area is formed on the surface of the substrate; (2) as shown in Figure 5 , the chip is directly welded to the electrode welding point of the die bonding area through tin-silver solder paste, and the installation angle of the chip is adjusted to 22°. (3) The substrate surface is photoetched with a microchannel array, the capillary force drives the filling of cadmium selenide / zinc sulfide quantum dot solution, spin-coating ZIF-8 metal organic framework precursor, in-situ crystallization at 180°C to form a 500 nm porous protective layer, covering the doped fluorescent powder with a thiuram silicone adhesive, curing at 150°C for 30 minutes to form a quantum dot optical layer; (4) Using thiuram silicone adhesive as the matrix, doping 12wt% nano ZrO2 and 8wt% fluorine modified polyimide microspheres, adding 4wt% SiO2@TiO2 core-shell light diffuser, mixing and vacuum degassing, degassing for 5 minutes at-0.1 MPa, injecting into the lens mold and forming a refractive index gradient with a gradient centrifugal program, then UV pre-curing to lock the gradient distribution, and finally heat curing at 150°C for 20 minutes to complete the packaging of the quantum dot optical layer; (5) Punch PCT / LCP alloy to form a stepped bowl cup structure, and magnetron sputtering Ag reflective layer on the inner wall; (6) The aluminum heat sink adopts a hollow split grid, the ceramic substrate is embedded in the stepped bowl cup, and the thiuram silicone adhesive filled with 70wt% aluminum nitride forms a vertical heat conduction and horizontal heat dissipation double channel; (7) The back of the ceramic substrate is welded with a linear driver by active metal brazing process; (8) Using 3D direct writing technology to precisely coat the thiuram silicone adhesive base layer outside the Micro-LED chip, quantum dot optical layer and electrode structure, and then printing the super lens array directly on the surface of the thiuram silicone adhesive layer through a 200 nm precision nozzle.
[0114] In step (2), the tin content of the tin-silver solder paste is 96.5%, and the silver content is 3.5%.
[0115] In step (3), the concentration of cadmium selenide / zinc sulfide quantum dot solution is 2000 μg / L, the molar concentration of fluorescent powder doping is 0.115 mol / L, and the thickness is 0.5 mm.
[0116] In step (3), the fluorescent powder includes KSF:Mn 4+ Red powder and LuAG:Ce 3+ Green powder, KSF:Mn 4+ Red powder: LuAG:Ce 3+ Green powder = 1:1, KSF:Mn 4+ Red powder: LuAG:Ce 3+ Green powder = 1:1.
[0117] In step (4), the gradient centrifugation process is 0 to 2000 rpm for 2 minutes, and then the speed is increased to 3000 rpm for 3 minutes.
[0118] In step (4), the UV pre-curing process is a preliminary irradiation of the material by a UV light source with a wavelength of 365 nm for 10 seconds.
[0119] In step (7), the linear driver model is Nanxi Micro NSL21924.
[0120] In step (7), the height of the superlens is 5 μm, and the period is 2 μm.
[0121] The LED lamp bead of Example 5 is subjected to CIE1931 calculation of color gamut coverage, and the light extraction efficiency is calculated by comparing the internally generated light power with the actual output light power. The temperature change curve with time is recorded by applying a short power pulse, the thermal resistance distribution is analyzed by using the structure function, the accelerated aging test is simultaneously performed, the light decay rate is measured after continuous operation for 1000 hours under constant current driving, and the service life is calculated, so as to obtain the specific performance parameters of the LED lamp bead of Example 5. The numerical values are compared with the typical value range of the industry, as shown in Table 5: Table 5: Comparison of numerical values of the LED lamp bead of Example 5 with the typical value range of the industry Index Example 5 LED lamp bead value Ordinary LED lamp bead Luminous efficiency 235 lm / W < 120 lm / W Light decay rate 1.2% / 1000 hours > 20% / 1000 hours Service life 150,000 hours 20,000 hours Color gamut coverage NTSC 135% NTSC 70-85% Thermal resistance 1.2K / W > 5K / W Drive response 1 μs > 10 μs Light extraction efficiency 96% 60-70% Example 5 is used as a control group of Example 4. Compared with Example 4, Example 5 increases the concentration of cadmium selenide / zinc sulfide quantum dot solution and the amount of SiO2@TiO2 added, and increases the height of the superlens, so as to increase the luminous efficiency, increase the color gamut coverage, reduce the light decay, and increase the light extraction efficiency.
[0122] The application also provides an LED lamp strip. The LED lamp strip is composed of a transparent conductive substrate, a light-emitting unit, a quantum dot optical layer, a gradient packaging body, a light-heat integrated structure, and an LED lamp bead and a patch resistor composed of a driving and optical control. The LED lamp strip is connected through a series-parallel circuit, and is covered by a waterproof silicone packaging layer and an optical lens.
[0123] Compared with Example 1, Example 2 significantly improves the light extraction efficiency and reduces the light decay rate by optimizing the chip mounting angle. The principle is that increasing the inclination angle can reduce the loss of total reflection, and at the same time, the heat distribution is more uniform, the in-situ crystallization temperature is increased to promote the formation of a dense porous protective layer of ZIF-8, effectively block the penetration of water and oxygen, reduce the light decay, and release the interfacial stress; the nano ZrO2 constructs a gradient refractive layer by high refractive index to reduce light scattering, and its high thermal conductivity cooperates with aluminum nitride glue to strengthen vertical heat dissipation; the fluorine-modified polyimide microsphere has low surface energy characteristics to inhibit interfacial scattering, high temperature resistance, and ensures high temperature stability; the SiO2@TiO2 core-shell light diffuser optimizes the light field distribution by Mie scattering principle, and its mechanical enhancement reduces the risk of packaging cracking, so as to increase the service life of the lamp bead.
[0124] Compared with Example 2, the increase of the chip mounting angle can significantly improve the luminous efficiency and reduce the light decay, the principle of which is that the inclined side wall can reduce the loss of total reflection, so that more photons escape from the side, the light extraction efficiency is improved, and the heat distribution is optimized, and the junction temperature is reduced; the increase of the amount of aluminum nitride fills the vertical heat dissipation channel by its high thermal conductivity, reduces the thermal resistance, thereby inhibiting material aging and improving stability; the increase of the concentration of cadmium selenide / zinc sulfide quantum dot solution can increase the area of the triangle formed by the three primary colors of red, green and blue by enhancing the photoluminescence intensity and color purity, so as to improve the color gamut coverage, and the high-efficiency light-emitting characteristics of quantum dots reduce energy loss, further reducing thermal resistance.
[0125] Compared with Example 3, the increase of the in-situ crystallization temperature can significantly improve the luminous efficiency and reduce the light decay, the mechanism of which is that high temperature promotes the formation of dense porous structure of ZIF-8 and other metal organic frameworks, effectively blocks the penetration of water and oxygen, reduces the non-radiative recombination caused by quantum dot oxidation, and at the same time relieves the interface stress caused by the mismatch of thermal expansion coefficient, thereby improving the stability; nano ZrO2 reduces light scattering by building a gradient refractive layer with high refractive index, and its high thermal conductivity cooperates with aluminum nitride to form a vertical heat dissipation channel, which significantly reduces the thermal resistance and inhibits material aging caused by the rise of junction temperature; fluorine-modified polyimide microspheres reduce bubbles and defects in the encapsulation layer by virtue of their low surface energy characteristics, inhibit photon scattering loss, and at the same time their high temperature resistance maintains the integrity of the optical structure and delays yellowing of the encapsulation material; the increase of the concentration of cadmium selenide / zinc sulfide quantum dot solution can enhance the photoluminescence intensity and color purity, and the high-efficiency light-emitting of quantum dots reduces energy loss, further reduces thermal resistance and prolongs service life.
[0126] Compared with Example 4, the increase of the concentration of cadmium selenide / zinc sulfide quantum dot solution can increase the density of light-emitting centers in unit volume, and the size effect of quantum dots can precisely regulate the emission wavelength, thereby improving the color purity and expanding the coverage range of CIE color coordinates; at the same time, the increase of the amount of SiO2@TiO2 core-shell structure can optimize the light field distribution through its core-shell scattering effect, reduce the loss of total reflection, and improve the light extraction efficiency, in addition, the increase of the height of superlens can enhance the interaction path of photons and quantum dots, combined with the high quantum yield of core-shell quantum dots and the interface passivation effect of SiO2@TiO2, non-radiative recombination is effectively inhibited, and the light decay rate is reduced.
[0127] The application provides a preparation method of an LED lamp bead, by adopting a high-purity alumina substrate with a thermal expansion coefficient matched with a Micro-LED chip, combining a magnetron sputtering deposited indium tin oxide dual functional electrode layer, forming a submicron circuit pattern through 365nm ultraviolet light etching and aqua regia wet etching, improving the substrate thermal conductivity, reducing the thermal resistance, and reducing the interface reflection loss through refractive index gradient matching; flip chip adopts Sn-Ag eutectic soldering instead of gold wire bonding, reduces the series resistance, and improves the light efficiency through the inclination design; a micro-channel array forms a capillary structure through deep reactive ion etching to realize quantum dot solution self-filling; a ZIF-8 porous layer fixes quantum dots through Zn 2+ -S coordination bond, a thiosiloxane glue constructs a flexible support skeleton, improves the color gamut coverage, and prolongs the service life; nano ZrO2 and SiO2@TiO2 core-shell particles construct a vertical heat conduction network, thiosiloxane glue filled with aluminum nitride forms Si-O-Al covalent bond, and the vertical thermal conductivity is improved; a PCT / LCP alloy ladder bowl cup and a topologically optimized aluminum mesh constitute a double-channel heat dissipation, so that the junction temperature is reduced; a superlens array realizes 15° light emission angle regulation and control through 200nm nozzle 3D printing; fluorine modified polyimide microspheres form a hydrophobic barrier, and the device life is increased in a humid heat environment through a UV curing process; a 3D direct writing packaging layer is chemically bonded with the chip electrode through a thiol group, the interface shear strength is improved, and the light efficiency is improved, thereby solving the problems of poor heat dissipation, low light efficiency, uneven light emission and short service life of the LED lamp bead.
[0128] Although the embodiments of the application have been shown and described above, it should be understood that the above-described embodiments are exemplary, and should not be construed as limiting the application, and those skilled in the art can make changes, modifications, replacements and variations to the above-described embodiments within the scope of the application.
Claims
1. An LED lamp bead, characterized in that, The LED lamp bead includes: a transparent conductive substrate, a light-emitting unit, a quantum dot optical layer, a gradient package, a photothermal integrated structure, and driving and optical control.
2. The method for preparing an LED lamp bead according to claim 1, characterized in that, Includes the following steps: (1) A high-purity alumina transparent ceramic substrate is selected, an indium tin oxide thin film layer is deposited by magnetron sputtering, a microelectrode circuit is formed by photolithography etching, and an array of die-bonding areas is photolithographically formed on the surface of the substrate. (2) A flip-chip Micro-LED is used and directly soldered to the electrode solder joint of the die bond area using tin-silver solder paste, and the chip mounting tilt angle is adjusted to 15°-30°. (3) The substrate surface is photolithographically arranged with microchannel array, capillary force drives the filling of cadmium selenide / zinc sulfide quantum dot solution, spin-coating ZIF-8 metal-organic framework precursor, in-situ crystallization at 150-180℃ to form a 500nm porous protective layer, covered with phosphor-doped thiosiloxane adhesive, cured at 150℃ for 30 minutes to form a quantum dot optical layer. (4) Thiosiloxane adhesive is used as the matrix, doped with 8-12wt% nano ZrO2 and 4-8wt% fluorine-modified polyimide microspheres, and 2-4wt% SiO2@TiO2 core-shell light diffusing agent is added. After mixing, vacuum degassing is performed at -0.1MPa for 5 minutes. The mixture is then injected into a lens mold and a refractive index gradient is formed by gradient centrifugation. Subsequently, UV pre-curing is performed to lock the gradient distribution, and then thermal curing is performed at 150℃ for 20 minutes to complete the encapsulation of the quantum dot optical layer. (5) A stepped cup structure is formed by stamping PCT / LCP alloy, and an Ag reflective layer is sputtered on the inner wall by magnetron sputtering; (6) The aluminum heat sink adopts a hollowed-out split grid, and the ceramic substrate is embedded in a stepped cup and filled with 60-70wt% aluminum nitride thiosiloxane glue to form a dual channel for vertical heat conduction and horizontal heat dissipation. (7) The linear actuator is soldered to the back of the ceramic substrate using an active metal brazing process; (8) Using 3D direct writing technology, a thiosiloxane adhesive base layer is precisely coated on the outside of the Micro-LED chip, quantum dot optical layer and electrode structure. Then, a superlens array is directly printed on the surface of the thiosiloxane adhesive layer using a 200nm precision printhead.
3. The method for preparing an LED lamp bead according to claim 2, characterized in that, The tin-silver solder paste in step (2) contains 96.5% Sn and 3.5% Ag.
4. The method for preparing an LED lamp bead according to claim 2, characterized in that, In step (3), the concentration of the cadmium selenide / zinc sulfide quantum dot solution is 800-2000 μg / L, the phosphor doping molar concentration is 0.115 mol / L, and the thickness is 0.5 mm.
5. The method for preparing an LED lamp bead according to claim 2, characterized in that, The phosphor in step (3) includes KSF:Mn 4+ Pink and LuAG:Ce 3+ Green powder, KSF:Mn 4+ Red Pink: LuAG:Ce 3+ Green powder = 1:
1.
6. The method for preparing an LED lamp bead according to claim 2, characterized in that, The gradient centrifugation process in step (4) is to gradually increase the speed from 0 to 2000 rpm for 2 minutes, and then increase the speed to 3000 rpm for 3 minutes to reach a steady state.
7. The method for preparing an LED lamp bead according to claim 2, characterized in that, The UV pre-curing process in step (4) involves irradiating the material with a UV light source with a wavelength of 365nm for 10 seconds.
8. The method for preparing an LED lamp bead according to claim 2, characterized in that, The linear driver in step (7) is model NSL21924 from Nanochip.
9. The method for preparing an LED lamp bead according to claim 2, characterized in that, The height of the superlens in step (7) is 3-5 μm.
10. An LED light strip, characterized in that, The LED light strip consists of a transparent conductive substrate, a light-emitting unit, a quantum dot optical layer, a gradient encapsulation body, a photothermal integrated structure, and LED beads and chip resistors that are driven and optically controlled. These components are connected through series and parallel circuits and covered with a waterproof silicone encapsulation layer and an optical lens.